2020
DOI: 10.1007/s40145-019-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of two-dimensional lead-free (K, Na)NbO3 micro/nano piezoelectric structures

Abstract: Two-dimensional (2D) lead-free (K, Na)NbO 3 (KNN) micro/nano structures with controllable K/Na ratio were successfully fabricated via a two-step molten salt synthesis (MSS). In this work, the reaction factors, including the proportion of molten salts, the types of carbonates, the sintering temperature, and the sintering time, were discussed in detail and the optimized condition was identified. The microstructure of KNN was confirmed by confocal Raman spectroscopy, while piezoresponse force microscopy (PFM) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Potassium sodium niobate ((K,Na)NbO 3 , KNN)-based ceramics are regarded as one of the most promising lead-free piezoelectric ceramics owing to their excellent piezoelectric response and high Curie temperature. [23][24][25][26] To achieve the desired properties of the KNN-based ceramics, doping is a mostly used way to tune their phase compositions, microstructures, and electrical performances. [27][28][29] For example, ZrO 2 is recently served as a dopant into KNN ceramics to suppress the grain growth and manipulate the piezoelectric properties.…”
Section: Methods Of Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium sodium niobate ((K,Na)NbO 3 , KNN)-based ceramics are regarded as one of the most promising lead-free piezoelectric ceramics owing to their excellent piezoelectric response and high Curie temperature. [23][24][25][26] To achieve the desired properties of the KNN-based ceramics, doping is a mostly used way to tune their phase compositions, microstructures, and electrical performances. [27][28][29] For example, ZrO 2 is recently served as a dopant into KNN ceramics to suppress the grain growth and manipulate the piezoelectric properties.…”
Section: Methods Of Characterizationmentioning
confidence: 99%
“…Potassium sodium niobate ((K,Na)NbO 3 , KNN)‐based ceramics are regarded as one of the most promising lead‐free piezoelectric ceramics owing to their excellent piezoelectric response and high Curie temperature 23–26 27–29 .…”
Section: Introductionmentioning
confidence: 99%
“…[92] The light-emitting properties can be flexibly tuned by the management of the energy-level alignment between the organic and organic components. When the exciton level of the inorganic layer is located above the singlet level of organic spacers, the luminescence of 2D perovskites is mainly dominated by the OC [108,109] PV [110,111] MG [112] FE [113,114] CO [115] PZE [116] 1D -LM [17,117] FE [118,119] FM [120] 0D [121,122] PV [123] FE [124] a) E g (bandgap), e (electronic effective mass), m h (hole effective mass), E b (exciton binding energy), optoelectronic (OC), photovoltaic (PV), magnetic (MG), ferroelectric (FE), chiral optics (CO), piezoelectricity (PZE), luminescence (LM), ferromagnetism (FM). The E b is assessed by using a simple Wannier exciton model.…”
Section: Excitonic Characteristic and Luminescence Mechanism Of Ldpsmentioning
confidence: 99%
“…[28,29] Lanthanum cobaltate (LaCoO 3 , LCO) is a typical and representative perovskite cobalt oxide with the general formulation of ABO 3 , which has received the most attention in electrocatalytic OER due to its simple preparation process, distinctive electrical, structural, magnetic and catalytic characteristics. [30][31][32][33] However, the electrocatalytic activity of LCO is severely restricted, which is the result of the dissatisfactory adsorption of oxygen-containing intermediate due to inappropriate spin configuration of Co ions. [34] Previous work demonstrated that more than one A-site and/or B-site cation can be admitted into the perovskite structure since it possessed the admirable tolerance of lattice heterogeneity and mismatch between different metal (A/B)À O bond lengths.…”
Section: Introductionmentioning
confidence: 99%